2019
DOI: 10.1093/geronb/gbz072
|View full text |Cite
|
Sign up to set email alerts
|

A Coordinated Multi-study Analysis of the Longitudinal Association Between Handgrip Strength and Cognitive Function in Older Adults

Abstract: Objective Handgrip strength, an indicator of overall muscle strength, has been found to be associated with slower rate of cognitive decline and decreased risk for cognitive impairment and dementia. However, evaluating the replicability of associations between aging-related changes in physical and cognitive functioning is challenging due to differences in study designs and analytical models. A multiple-study coordinated analysis approach was used to generate new longitudinal results based on c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

3
51
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 59 publications
(55 citation statements)
references
References 69 publications
3
51
0
1
Order By: Relevance
“…Age-associated cognitive impairment, which is the loss of intellectual functions, such as thinking, remembering, reasoning, and planning, with age, can have considerable negative effects on the forcegenerating capacity of skeletal muscles (6). These effects may be mediated by the negative influence of impaired cognition on neuromotor control.…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…Age-associated cognitive impairment, which is the loss of intellectual functions, such as thinking, remembering, reasoning, and planning, with age, can have considerable negative effects on the forcegenerating capacity of skeletal muscles (6). These effects may be mediated by the negative influence of impaired cognition on neuromotor control.…”
mentioning
confidence: 99%
“…These effects may be mediated by the negative influence of impaired cognition on neuromotor control. There is now substantial evidence to suggest an association among hand grip strength, gait speed, and cognition (6)(7)(8). For example, a recent meta-analysis including 9 longitudinal studies in older adults showed a positive correlation (overall r=0.55) between changes in hand grip strength and changes in cognitive function (6).…”
mentioning
confidence: 99%
See 3 more Smart Citations